1988
DOI: 10.1038/336496a0
|View full text |Cite|
|
Sign up to set email alerts
|

An eIF-4A-like protein is a suppressor of an Escherichia coli mutant defective in 50S ribosomal subunit assembly

Abstract: The assembly of ribosomes in bacterial cells is a complex process that remains poorly characterized. The in vitro assembly of active ribosomal subunits from purified RNA and protein components indicates that all of the information for proper assembly resides in the primary sequences of these macromolecules. On the other hand, the in vitro requirement of unphysiological heating steps suggests that this pathway may not accurately reflect the in vivo pathway, and that other proteins may be required. One approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(98 citation statements)
references
References 16 publications
4
93
0
1
Order By: Relevance
“…The nucleotide sequences of mammalian eIF4A cDNA and the yeast eIF4A encoding genes (Linder and Slonimski, 1988;Nielsen et al, 1985;Nielsen and Trachsel, 1988) are 65% identical and 81% similar, suggesting a functional conservation in translation initiation. The analysis of these protein sequences was extended by the publication or personal communication of similar protein sequences (PL10, vasa, MSS116, SrmB, p68;Ford et al, 1988;Lasko and Ashburner, 1988;Leroy et al, 1989;Nishi et al, 1988;Séraphin et al, 1989). At the time all these proteins were reported to be required for processes involving RNA molecules.…”
Section: The Eif4a Protein-the Prototype Of the Dead-box Familymentioning
confidence: 99%
“…The nucleotide sequences of mammalian eIF4A cDNA and the yeast eIF4A encoding genes (Linder and Slonimski, 1988;Nielsen et al, 1985;Nielsen and Trachsel, 1988) are 65% identical and 81% similar, suggesting a functional conservation in translation initiation. The analysis of these protein sequences was extended by the publication or personal communication of similar protein sequences (PL10, vasa, MSS116, SrmB, p68;Ford et al, 1988;Lasko and Ashburner, 1988;Leroy et al, 1989;Nishi et al, 1988;Séraphin et al, 1989). At the time all these proteins were reported to be required for processes involving RNA molecules.…”
Section: The Eif4a Protein-the Prototype Of the Dead-box Familymentioning
confidence: 99%
“…In fact, the srmB gene was originally isolated as a multicopy suppressor of mutations in the ribosomal protein L24 gene rplX. 81 Deletion of srmB results in (1) slow-growth phenotype at low temperature, (2) deficit in free 50S ribosomal subunits and (3) accumulation of a new ribosomal particle sedimenting around 40S. Thus, it was suggested that there is a step of 50S assembly, which involves a structural rearrangement that, at least at low temperature, requires SrmB.…”
Section: Helicases and Exoribonucleasesmentioning
confidence: 99%
“…Two of these proteins, DeaD and SrmB, are implicated in ribosome assembly, since each factor associates with ribosomal subunits, and the absence of either protein causes ribosome biogenesis defects (Charollais et al 2003(Charollais et al , 2004. Both factors were initially identified as multicopy suppressors of ribosomal protein mutants (Nishi et al 1988;Toone et al 1991). Among the remaining three DEAD-box proteins, one, DbpA has been shown biochemically to interact with 23S ribosomal RNA (rRNA), the major RNA component of large ribosomal subunit (Fuller-Pace et al 1993).…”
Section: Introductionmentioning
confidence: 99%